2009
DOI: 10.1016/j.ejcts.2009.02.055
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of elderly patients following valve surgery for chronic organic mitral regurgitation☆

Abstract: Quality of life following mitral valve surgery is suboptimal in more than half of elderly patients. MLHF score at follow-up is mostly related to preoperative conditions. Type of surgery does not influence MLHF score, however, quality of life is worse in patients with recurrent/residual MR following repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…This effect was observed on top of optimal medical therapy and in highly symptomatic patients: as opposed to EVEREST II, with 49% of patients in NYHA functional class I or II, we included only patients in NYHA functional class III or IV. Also, MLHFQ score improved by almost 20 points, which is comparable with results reported for MV surgery (7). In accordance, 6-min walk distance increased in 75% of our patients, further underscoring the profound clinical benefit derived from this therapy in the majority of patients included.…”
supporting
confidence: 92%
“…This effect was observed on top of optimal medical therapy and in highly symptomatic patients: as opposed to EVEREST II, with 49% of patients in NYHA functional class I or II, we included only patients in NYHA functional class III or IV. Also, MLHFQ score improved by almost 20 points, which is comparable with results reported for MV surgery (7). In accordance, 6-min walk distance increased in 75% of our patients, further underscoring the profound clinical benefit derived from this therapy in the majority of patients included.…”
supporting
confidence: 92%
“…Immer et al [24], on the contrary, using SF-36 questionnaire, did not find any difference between QoL after mitral valve replacement or repair in a series of 115 patients at 3 years after surgery, although inhospital mortality was significant higher in replacement than in repair patients. Also Maisano et al [25] concluded that the type of surgical technique does not influence QoL at follow-up, but perceived selfhealth is worse in patients with recurrent/residual MR following repair.…”
Section: Discussionmentioning
confidence: 98%
“…Though operative risks of mitral valve surgery reduced significantly during the last decades [20], however quality of life after such surgical interventions, a factor of great importance in the elderly population has rarely been reported. Maissano et al [21] found that quality of life was suboptimal in more than half of elderly patients following mitral valve surgery and that surgical technique did not impact quality of life at follow up. They identified several factors significantly related to increased Minnesota Living With Heart Failure (MLHF) - score at follow-up after valve surgery in the elderly.…”
Section: Discussionmentioning
confidence: 99%